PROBLEMS OF IMPOSITION OF CRIMINAL PUNISHMENT ALTERNATIVE TO IMPRISONMENT - T. V. Nepomnyashchaya (Правоприменение)
The subject. The article is devoted to problems of appointment some criminal punishments alternative to the deprivation of liberty by courts in Russian Federation. The author gives an answer to the question, why punishments not related to imprisonment in the Russian Federation, especially deprivation of the right to occupy certain positions or engage in cer-tain activities, corrective labor, restriction of freedom, forced labor, are rarely appointed by courts, and the most common alternative punishments are only fine and mandatory work.Methodology. Author uses such researching methods as analysis and synthesis, formally legal, comparative legal.Results. The author proposes some concrete measures, aimed at expanding the practice of appointment some criminal punishments alternative to the deprivation of liberty.It is necessary to reduce the size of the fine established in the Criminal Code of the Russian Federation. It is necessary to establish a penalty in the sanction of norms on crimes of small and medium gravity, committed for mercenary motives and connected with causing mate-rial damage.In order of more effective serving of punishments in the form of compulsory and corrective works, it is necessary to interest employers, it can be expressed in granting tax credit ben-efits. The searching of specific facilities for serving corrective labor should be assigned to employment centers.It seems expedient to introduce deprivation of the right to occupy certain positions or en-gage in certain activities as the main type of punishment to all sanctions of the norms about the responsibility for crimes of small or medium gravity related to the professional activities of the person. It is necessary to eliminate gaps in the legislative regulation of punishment in the form of restricted liberty and to solve the problem of electronic monitoring of convicts using elec-tronic bracelets.Conclusions. The punishment in the form of deprivation of liberty should be appointed by courts only in cases, when the crime is highly dangerous, the identity of the criminal is also characterized by a high degree of public danger. Serious changes are also needed in the legislative regulation of sentences not related to deprivation of liberty, and a number of other organizational measures aimed at expanding the practice of applying these punish-ments.